Dielectric Behavior of α-Ag2WO4 and its Huge Dielectric Loss Tangent - Natalia Jacomaci; Euripedes Silva Junior; Fernando Modesto Borges de Oliveira; Elson Longo; Maria Aparecida Zaghete (Materials Research, 2019)
The microwave-assisted hydrothermal method was used to obtain α-Ag2WO4. Rietveld refinement confirmed that α-Ag2WO4 is stable in the orthorhombic phase, without secondary phase. However, field-effect scanning electron microscope analysis showed that α-Ag2WO4 nanorods surfaces contain silver nanoparticles, confirmed by the X-ray photoelectron spectroscopy by the peak observed at 374.39 eV. In addition to metallic Ag, other Ag oxidation states were also observed on the surface. Hence, Ag (I) as Ag2O and Ag (I) as Ag2WO4 also were identified. DC measurements exhibited a high capacity of charge storage, nevertheless, with a large loss tangent (0.12 µC.cm-2.V-1) and no residual polarization for the voltage range between -100 V and +100 V. AC measurements at frequencies less than 275 Hz, revealed that ionic polarization is dominant, whereas at frequencies higher than 275 Hz, the electronic behavior predominates. The potential of electromagnetic energy conversion in thermal was observed from loss tangent analysis.